The prisoners of Breendonk : personal histories from a World War II concentration camp - Deem, James M. (Houghton Mifflin Harcourt, 2020)
Presents the personal stories of prisoners at Breendonk, a concentration camp in Antwerp, Belgium, during World War II. Describes the camp's first prisoners and deaths, brutal reputation, liberation, officers' trials, and condition today. Includes access to camp archives, rare photographs and artwork, a map, and a glossary of terms.